2019
DOI: 10.1016/j.snb.2018.10.130
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the sensitivity in optical biosensing by striped arrays and frequency-domain analysis

Abstract: Highlights A simple signal processing based on frequency-domain analysis is introduced.  Identification and removal of the undesired noise contributions from the analytical signal.  Approach developed to enhance the sensitivity of optical biosensors.  Probe of concept determining immunoglobulins and casein through immunoassay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…From this image one then performs a digital Fourier transform and applies a digital bandpass filter (as in the time domain [ 18 ]). In biosensors, the digital lock-in approach has been demonstrated with sensors based on labeled molecules (e.g., the signal is mediated by a fluorophore) and the authors have reported significantly improved detection limits with the digital lock-in compared to integrative sensors [ 54 ]. In addition, any surface plasmon resonance imaging sensor using distributed referencing is essentially a digitally locked-in sensor [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…From this image one then performs a digital Fourier transform and applies a digital bandpass filter (as in the time domain [ 18 ]). In biosensors, the digital lock-in approach has been demonstrated with sensors based on labeled molecules (e.g., the signal is mediated by a fluorophore) and the authors have reported significantly improved detection limits with the digital lock-in compared to integrative sensors [ 54 ]. In addition, any surface plasmon resonance imaging sensor using distributed referencing is essentially a digitally locked-in sensor [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, flat polycarbonate plates were employed as substrates on to build this multilayered material. This polymer is easy to handle, presents a good adhesion for sputtered gold, and the bioanalytical developments on polycarbonate involve appealing lab-on-a-disk perspectives for labelled and label-free biosensing [23][24][25].…”
Section: Interferometric Nanomaterialsmentioning
confidence: 99%
“…However, a major challenge is interference from the nonspecific binding of nontarget proteins (e.g., background noise). Extra separation and purification techniques, such as centrifugation, desalting, filtration, and affinity depletion of other interfering molecules, were applied [ 12 , 13 ]. In the meantime, high-affinity reagents with a high selectivity to the target protein are required to reduce interference [ 14 ].…”
Section: Introductionmentioning
confidence: 99%